Implementasi Kebijakan Pencegahan Penyalahgunaan Narkoba di Kabupaten Pesisir Selatan - Putri, Popy Mullya; Yusran, Rahmadani (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2025)
This study analyzes drug abuse prevention policies in South Pesisir Regency, applying Edward III’s Policy Implementation Model. The research used a descriptive qualitative method, gathering data through interviews, observation, and documentation. Findings show that implementation faces significant hurdles across four key areas; Communication: Policy information is not consistently distributed and lacks a unified message. Resources: Budget and personnel for implementation are limited. Disposition: While individual implementers are committed, they lack institutional support and proper incentives. Bureaucratic Structure: The system is not integrated into a permanent, cross-sectoral governance framework. However, the